A National Analysis of Endowed Chairs and Distinguished Professors in the Field of Education. Issue 2 (3rd March 2016) - Hartlep, Nicholas Daniel; Ball, Daisy; Theodosopoulos, Kendra; Wells, Kevin; Morgan, Grant B.
Abstract : Noting a gap in the literature, this study examines how race, gender, and prestige are related to endowed and distinguished faculty of education. Specifically, this study seeks to ascertain the makeup of higher education with regard to faculty diversity: what processes are at work that serve to recreate the status quo in terms of faculty of higher education? Or, are higher education faculty members becoming more diverse as homogeneous cohorts retire and heterogeneous cohorts replace them? Using social network theory as a theoretical framework, several hypotheses were set forth. Original data ( n = 517) were collected and later analyzed using descriptive as well as inferential non-parametric statistics. The findings of this study are discussed as they relate to the research questions and hypotheses, informed by social network theory. Implications for higher education policy and practice are shared, and directions for future research are considered.